Geographical variation in morphology and its environmental correlates in a widespread North American lizard, Anolis carolinensis (Squamata: Dactyloidae). (4th November 2015) - Jaffe, Alexander L.; Campbell‐Staton, Shane C.; Losos, Jonathan B.
Abstract : The green anole, Anolis carolinensis, has long been an important model organism for studies of physiology and behaviour, and recently became the first reptile to have its genome sequenced. With a large and environmentally heterogeneous distribution, especially in relation to well‐studied Antillean relatives, A. carolinensis is also emerging as an important organism for novel studies of geographical differentiation and adaptation. In the present study, we quantify the degree of morphological variation in this species and test for environmental correlates of this variation. We also examine adherence to Bergmann's and Allen's rule, two eco‐geographical principles that have been well studied over large species ranges. We sampled from 14 populations across the distribution of the species in North America and measured 28 distinct morphological traits. We also collected a suite of environmental variables for each site, including those related to temperature, precipitation, and vegetation. Ultimately, we found a large degree of geographical variation in morphology, with head traits contributing the most to differences among populations. Morphological variation was correlated with variation in temperature, precipitation, and latitude across sites. We found no support for reverse Bergmann's rule typical of squamates, although we did find a trend of reverse Allen's rule. Ultimately, the present study provides a novel look at A. carolinensis and establishes it as a strong candidate for further studies of variation and adaptation over a large range.